"She gave me hope and lightened my heart": The transition to motherhood among vulnerable (young) mothers. (November 2020) - van Vugt, Eveline; Versteegh, Pleuntje
Highlights: Adverse childhood events (ACEs) continue to impact the transition to motherhood. Relationships with close family members were generally strained. Treatment should include the establishment of formal sources of social support. The ability to bond to the baby is sometimes delayed. Practitioners should be aware of behaviors/cognitions that reflect these delays. Abstract: The aim of the present study was to gain an understanding of how vulnerable mothers with adverse childhood experiences transition towards motherhood. Semi-structured interviews were conducted with a convenience sample of 15 vulnerable (young) mothers who were residing in a mother-baby home at the time of the study. By means of inductive thematic analyses, a number of themes were identified that characterized the transition to motherhood. The results showed that mothers experienced a number of adversities during childhood which made them aware early on what type of mother they wanted to be for their children. Because of medical complications or involvement of child protective services, the ability to take care and bond with the baby was sometimes delayed. Further, the arrival of the baby was often considered a turning point: to bring change to the life of the mother or a second chance to motherhood. Relationships with their own parents were generally strained and sometimes put on hold to protect oneself. The mothers also mentioned difficulties with accepting and asking for support, their outlook on social support was generally ambiguous. Clinical implications of the results are discussed in the light of traditional care and the theory on ambiguous loss.